Analyzing Students' Mathematical Spatial Literacy Using a Project-Based Blended Learning Model - Priatna, Nanang; Mustika Sari, Rika Mulyati (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
The application of project based blended learning in analyzing mathematical spatial literacy is described in this article. The research method used is descriptive quantitative. Participants in the study consisted of 33 students of class XI at one public high school in Bandung Regency. The type of research used is pre-experimental with a one-shot case study design, the subject is taken by simple random sampling using purposive sampling technique. Data analysis in this study is quantitative data analysis in the form of descriptive statistical tests and differential statistical tests. Based on the results of calculations using descriptive statistical tests that students in the high category were 10 students (3%), the medium category was 21 students (64%) and the low category was 2 students (6%). The results of the differential analysis for the normality test of the data are not normally distributed and from the results of the calculation of the median test obtained 0,0148782 ≥ 0,025, this means that the results of this test conclude that at a 95% confidence interval, the median mathematical spatial literacy ability of students after the Project based blended learning model is applied can reach KKM.Penerapan project based blended learning dalam menganalisis literasi spasial matematis dideskripsikan dalam artikel ini. Metode penelitian yang digunakan adalah deskriptif kuantitatif. Partisipan dalam penelitian terdiri dari 33 siswa kelas XI pada satu SMA Negeri Kabupaten Bandung. Jenis penelitian yang digunakan pre-experimental dengan desain one shot case study, subjek diambil secara simple random sampling dengan menggunakan teknik purposive sampling. Analisis data dalam penelitian ini adalah analisis data kuantitatif berupa uji statistik deskriptif dan uji statistik iferensial. Berdasarkan hasil perhitungan menggunakan uji statistik deskriptif bahwa siswa yang memiliki kategori tinggi 10 siswa (3%), kategori sedang 21 siswa (64%) dan kategori rendah 2 siswa (6%). Hasil analisis iferensial untuk uji normalitas data tidak berdistribusi normal dan dari hasil perhitungan uji median diperoleh 0,0148782 ≥ 0,025, ini berarti Hasil pengujian ini memberikan kesimpulan bahwa pada selang kepercayaan 95%, median kemampuan literasi spasial matematis siswa setela diterapkan model Project based blended learning dapat mencapai KKM.